Antibacterial soap use impacts skin microbial communities in rural Madagascar - Yu, James J.; Manus, Melissa B.; Mueller, Olaf; Windsor, Sarah C.; Horvath, Julie E.; Nunn, Charles L. (PLOS ONE, 2018)
The skin harbors diverse communities of microorganisms, and alterations to these communities can impact the effectiveness of the skin as a barrier to infectious organisms or injury. As the global availability and adoption of antibacterial products increases, it is important to understand how these products affect skin microbial communities of people living in rural areas of developing countries, where risks of infection and injury often differ from urban populations in developed countries. We investigated the effect of antibacterial soap on skin microbial communities in a rural Malagasy population that practices subsistence agriculture in the absence of electricity and running water. We quantified the amount of soap used by each participant and obtained skin swab samples at three time points: prior to soap use, immediately after one week of soap use, and two weeks after soap use was discontinued. Soap use did not significantly impact ecological measures of diversity and richness (alpha diversity). However, the amount of soap used was a predictor of community-level change (beta diversity), with changes persisting for at least two weeks after subjects stopped using soap. Our results indicate that the overall species richness of skin microbial communities may be resistant to short-term use of antibacterial soap in settings characterized by regular contact with the natural environment, yet these communities may undergo shifts in microbial composition. Lifestyle changes associated with the use of antibacterial soap may therefore cause rapid alterations in skin microbial communities, with the potential for effects on skin health.